PEMBUATAN APLIKASI TAGIHAN AIR DAN SAMPAH MENGGUNAKAN LONGTION APP BUILDER - Joefrie, Yuri Yudhaswana (FORISTEK : Forum Teknik Elektro dan Teknologi Informasi, 2015)
– This application is built for recording customer who already paid the bill or not. The business process for building this aplication is quite simple, to record customer, to record billing monthly, and to create report of cash flow. Longtion Application Builder is used to create the system, while Microsoft Access is used to create a database. After doing a literature study and interviewing a user, producing an application that consists of 7 forms for main operation as stated above. Beside forms, application need tables to store its data, the number of tables required for this application to work are 4.Keywords: Longtion software, Microsoft Access, Water and garbage bill application.